Integrating information science for sustainable development: topics and trends (Editora Oficina Universitária, 2025)
This book serves as a practical guide and comprehensive analysis of how Information Science can be integrated into sustainable practices, with insights spanning digital transformations, information behavior, knowledge organization, and more. The book explores the intersections between Information Science and sustainability from multiple perspectives, illustrating how libraries, information literacy, and digital tools contribute to building a sustainable future. It is a set of 27 chapters organized into five main parts, "21st Century Skills and the Information Profession", "Digital Transformation and Sustainability", "Information Behavior and Sustainability", "Libraries and Education for Sustainability" and "Knowledge Organization to Support Sustainability", which stem from the selection of presentations made at the 32nd BOBCATSSS Conference held at the University of Coimbra, Portugal from January 23 to 25, 2024 and co-organized by the São Paulo State University – UNESP, Marília Campus. Each part investigates the unique ways in which information workers are adapting to the demands of the 21st century and contributing to environmental and social well-being in different cultural and institutional contexts.